Ultra-lightweight superconducting wire based on Mg, B, Ti and Al - P. Kováč (Nature Portfolio, 2018)
Abstract Actually, MgB2 is the lightest superconducting compound. Its connection with lightweight metals like Ti (as barrier) and Al (as outer sheath) would result in a superconducting wire with the minimal mass. However, pure Al is mechanically soft metal to be used in drawn or rolled composite wires, especially if applied for the outer sheath, where it cannot provide the required densification of the boron powder inside. This study reports on a lightweight MgB2 wire sheathed with aluminum stabilized by nano-sized γ-Al2O3 particles (named HITEMAL) and protected against the reaction with magnesium by Ti diffusion barrier. Electrical and mechanical properties of single-core MgB2/Ti/HITEMAL wire made by internal magnesium diffusion (IMD) into boron were studied at low temperatures. It was found that the ultra-lightweight MgB2 wire exhibited high critical current densities and also tolerances to mechanical stress. This predetermines the potential use of such lightweight superconducting wires for aviation and space applications, and for powerful offshore wind generators, where reducing the mass of the system is required.